Women Identities’ Portrayal in Two Hemingway’s Selected Short Stories - Susanty (The Study Program of English Education of Palangka Raya University, 2021)
Previous studies on Hemingway are mostly about his major novels. The writer of the article therefore chose another form of Hemingway’s works, those are short stories. This article argues that it is important to read Hemingway’s works with the knowledge about his own complex characters. By reading the biographies, reader will learn more about Hemingway both as a man and a legend and his treatment to his female characters. This article intends to indicate to the readers that it is important to connect Hemingway’s theme about women identities in his stories to his own life because many parallels have been drawn.